Krafft phenomenon-based study of the polymer-surfactant interaction - Feitosa, Eloi [UNESP]; Camillo, Paulo C. [UNESP]; Adati, Renata D. (Springer Nature, 2023)
The Krafft phenomenon was exploited here as a novel method to investigate the polymer-surfactant interaction for a 35 kD poly(ethylene glycol) (PEG) and sodium dodecyl sulfate (SDS) in an aqueous solution. Partial phase diagrams in the water-rich corner (≥ 99 wt%) at 5 °C (below the Krafft point of SDS) for the PEG/SDS/water system in the presence of up to 100 mM NaBr, present a single isotropic (Iso) phase, indicating the presence of PEG-SDS complexes in equilibrium with SDS monomers, or an Iso phase plus hydrated crystals (HCs) depending on composition. The binodal indicates that the critical micelle concentration (CMC), the critical aggregation concentration (CAC), or the polymer saturation point (PSP) decreases with NaBr concentration, and more HCs are formed, indicating that less amount of SDS is bound to the polymer. Surface tension and electrical conductance data corroborate the CMC, CAC, or PSP values obtained from the binodals. In the presence of 100 mM NaBr, the mean hydrodynamic diameter (DH) of the PEG-SDS complexes (DH ≈ 9–12 nm), is larger than that of the polymer coil (DH ≈ 8 nm) and the SDS micelles (DH ≈ 4 nm). Since these results are compatible with others obtained from ordinary methods, the method based on the Krafft phenomenon introduced here is suitable to investigate other polymer-surfactant systems. Graphical Abstract: [Figure not available: see fulltext.].
Keywords: Krafft phenomenon; Phase behavior; Poly(ethylene glycol); Polymer-surfactant interaction; Sodium dodecyl sulfate